ANALISIS KANDUNGAN MERKURI (Hg) DAN KADMIUM (Cd) PADA BEBERAPA JENIS IKAN ASIN YANG DI PRODUKSI DI KELURAHAN BAHARI KECAMATAN MEDAN BELAWAN TAHUN 2015 - irene silitonga; wirsal hasan; evi naria (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Salted fish is one of fishery products that have an important position and also is one of the nine basic foods on a national scale.Curring aims that preserve the fish doesn’t relieves metal properties. Metal properties can not demolished. Metal will dissolved in the water and absourbed by microoganism then eaten by fish and finally that’s happen bioaccumulation and biomagnification so that fish which make processing, it doesn’t relieve metal properties that contained the fish. The method used in this research is descriptive survey. Samples were obtained from salted fish producers in kelurahan Bahari, Subdistrict of Medan Belawan, checked in Health Laboratory, Province of North Sumatra and Center for Research and Industry of Medan.The five samples of salted fish are ikan Lemuru (Sardinella Aurta), ikan Gelama (Pseudoceina amoyensis), ikan Kresek(Trissa mytax), ikan Gembung (Restreluger kenagona), dan ikan Cincaru (Eleutheronema aurta). To determine the content of mercury (Hg) and Cadmium (Cd) is performed by Spektrofotometri Serapan Atom(SSA) method. To result showed that the content of Mercury (Hg) in salted fish produced in Kelurahan Bahari has been qualified according to BPOM in 2009, which is 0.5 ppm. The content of Cadmium (Cd) contained in a salted fish which exceed the NAB set by BPOM, namely Lemuru fish 0.480 ppm.The four different salted that fish are qualify according to BPOM in 2009, which is 0.1 ppm. Society may consume salted fish produced in Kelurahan Bahari with the exposure limit and not constantly